The Effectiveness of Digital Media in 21st Century Mathematics Subjects to Improve Learning Outcomes in Boarding Schools - Rosidin Rosidin; Herpratiwi Herpratiwi; Sugeng Sutiarso; Muhammad Nurwahidin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Efforts to improve the quality of Islamic boarding schools are increasingly urgent and unavoidable. The free market era that has rolled out demands the ability to compete from our human resources. The problem of declining math learning outcomes in boarding schools is influenced by the lack of innovation and creativity of boarding school teachers in providing learning facilities for students. This study aims to determine the effectiveness of digital media in 21st Century Mathematics subjects to improve learning outcomes in Islamic boarding schools. The method used in this research is quantitative with a case control approach. Data analysis conducted in this study was carried out by looking at the results of the pretest and posttest after treatment, by looking at the results of the Gain normality test. The sample in this study amounted to 30 people considering that the sample was homogeneous in class VIII. the results of research and discussion of digital media can be seen to increase by 70% in math learning outcomes. Digital media provides a role to make it easier for students to understand concepts such as visualizing complex mathematical concepts, digital media can bring mathematics into the context of real life.